Testing the cross-cultural generalizability of the scale of consumer attitudes toward marketing and consumerism - (:unkn) unknown (My University, 1996)
The literature includes many studies on consumer attitudes toward marketing and/or business practices, and consumerism. Since such research hsa either developed/validated scales/instruments or used the scales in previous studies without any change, their cross-cultural generalizability requires further research. Consequently, this study deals with the recommended methodology for testing the cross-cultural generalizability of the scale of consumer attitudes toward marketing and consumerism developed by the Barksdale and Darden (1972) as a major study used by researchers. Since the examination of the scale's psychometric properties (i.e., dimensionality and reliability) did not offer general support for the scale's applicability to the Turkish sample, the 40 items of Barksdale and Darden (1972) were factor analyzed and ten extracted factors were re-defined to measure Turkish consumers' (i.e., undergraduate business students) attitudes toward marketing practices and consumerism. It is also pointed out that there are some differences and similarities between the study of Barksdale and Darden (1972) and previous studies in which the slightly modified version of the original scale was used as well as the present study. © 1996 Taylor & Francis Group, LLC.